2009
DOI: 10.1111/j.1468-1331.2009.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic posterior circulation stroke in State of Qatar

Abstract: The aetiology and lesion topography of PCS in this heterogeneous population differs from the pattern observed in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
2
40
2
1
Order By: Relevance
“…Previous studies, the New England Medical Center Posterior Circulation Registry, and a Qatar study presented within-study comparisons of the frequency of the neurological deficits in PCI cohorts; but, these studies did not compare PCI with ACI patients. 11,18 The frequency appeared to vary in some clinical manifestations in these previous studies, as compared with that in our study; however, homolateral paralysis and facial palsy were also found previously to be the most common signs in PCI patients. The divergent frequencies may partly caused by differences in the severity of vertebrobasilar ischemia among stroke populations 11 and the different definitions studies used when classifying the neurological deficits.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Previous studies, the New England Medical Center Posterior Circulation Registry, and a Qatar study presented within-study comparisons of the frequency of the neurological deficits in PCI cohorts; but, these studies did not compare PCI with ACI patients. 11,18 The frequency appeared to vary in some clinical manifestations in these previous studies, as compared with that in our study; however, homolateral paralysis and facial palsy were also found previously to be the most common signs in PCI patients. The divergent frequencies may partly caused by differences in the severity of vertebrobasilar ischemia among stroke populations 11 and the different definitions studies used when classifying the neurological deficits.…”
Section: Discussioncontrasting
confidence: 40%
“…28 Similarly, 2 recent studies showed that the prevalence of altered level of consciousness in PCI patients was much lower (Ͻ10% and 18%, respectively) than was suggested by previous studies. 11,18 These controversies might be caused by a different distribution of stroke subtypes or different age groups. At the least, the present study revealed that additional investigations are required to determine whether consciousness disturbance should be considered diagnostic for PCI.…”
Section: Tao Et Al Posterior Versus Anterior Circulation Infarction 2063mentioning
confidence: 99%
“…When reported, common types of acquired nystagmus are gaze evoked, multi-vector and upbeat [66]. The studies described to date, frequently report when the stroke has affected the posterior circulation, including the cerebellum [42, 60,67,68]. No studies have reported the prevalence of nystagmus in anterior circulation strokes in isolation.…”
Section: Nystagmusmentioning
confidence: 99%
“…According to our results, we can suggest two reasons for these misdiagnoses of WS. First, the characteristic symptoms of WS are rather mild; it has been reported that the severity of brainstem infarction is relatively low and prognosis is good (Glass et al., 2002; Akhtar et al., 2009; Fitzek et al., 2001). Indeed, the mean NIHSS score of our patients with WS was also as low as 3.1, and some patients came to the outpatient clinic by foot and with only minor complaints.…”
Section: Discussionmentioning
confidence: 99%